Mechanics and relativity - Soni, Vidwan Singh (PHI Learning, 2011)
"This book provides a comprehensive introduction to the fundamental principles and concepts of Classical, Newtonian, and Relativistic Mechanics. It seeks to explain the basic concepts of these areas of physics in a concise manner. The book is primarily meant to serve the requirements of the first year undergraduate (B. Sc.) students of physics ... In this edition, the treatment of several concepts covered in the earlier edition has been expanded, and new exercises and several multiple choice questions have been added"--Publisher's description.